Farm Households and Wage Labour in the Northeastern Maritimes in the Early 19th Century - Bittermann, Rusty (Labour/Le Travailleur, 1993)
This paper underlines the significance of farm dwellers to the wage labour force during the first half of the 19th century. It begins with a consideration of the influences which led farm dwellers in the northeast Maritimes to seek wage work. It then examines the types of work that they became involved with, emphasizing the variety in their work experiences, both in local and in distant settings. It concludes with a consideration of some of the consequences that followed from the involvement of farm dwellers in wage labour.